Dare to be different / Norailis Ab. Wahab ... [et al.] - Ab. Wahab, Norailis; Abdul Rahim, Syarizal; Che Razak, Razli; Ismail, Mohammad (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
"Move along with MOFAZ" is the company's philosophy since its inception 43 years ago. The business began as a distributor of NESTLE products. Now, it has thrived with various business ventures under its wing. MOFAZ and its many business partners and vendors grow together under a firm belief in self-discipline, competence, hard work, and respect for others. Having established its standing in the industry, MOFAZ's focus in its second decade is 'Dedication towards Excellence', aiming to produce superior products and services in the automotive, agricultural, and food industries. MOFAZ has maintained its competitiveness throughout its journey, starting from the NESTLE Distributor Coalition to MOFAZ Air, which became the foundation for the world-renowned Air Asia. The study has identified several critical criteria of how MOFAZ remains competitive in the market. They are People, Culture, Process, Knowledge, Technology, and Capital, which are described by the authors through the experiences of the President of MOFAZ Group, Fauzy. The company, likewise, has faced several obstacles. They come in at least two forms: external (e.g., inter-organizational politics) and internal (e.g., the fear of investing). Business changes are always unpredictable. Even so, Fauzy tried to keep a positive mindset and sustained during the economic downturn. However, once in a while, a big trend may come along and break all conventions. Fauzy upheld MOFAZ's competitive advantage through its history and networking. After getting great opportunities, he continued to publicize MOFAZ's gains by announcing its recent performance on various media platforms. Sustainability is one such trend.